Electrospun PCL/GO-g-PEG structures: Processing-morphology-properties relationships. (January 2017) - Scaffaro, Roberto; Lopresti, Francesco; Maio, Andrea; Botta, Luigi; Rigogliuso, Salvatrice; Ghersi, Giulio
Abstract: Polycaprolactone (PCL) biocomposite nanofiber scaffolds with different concentrations of graphene oxide (GO) and GO surface grafted with poly(ethylene glycol) (GO-g-PEG) were prepared by electrospinning. Morphological, mechanical as well as wettability characterizations of electrospun nanofibers were carried out. Results showed that the average diameter of PLA/GO electrospun nanofibers decreased upon increasing the filler content. Differently, the diameter increased while using GO-g-PEG. Both nanofillers enhanced the electrospun PCL hydrophilicity even if PCL/GO-g-PEG samples exhibited improved wettability. The Young moduli of the composite nanofiber mats were improved by adding GO, and it was further enhanced when GO was surface grafted with PEG, in particular at low concentrations. This suggests the improved dispersion of GO-g-PEG due to the surface grafting with PEG. Furthermore, in order to assess the potential applications of the electrospun nanofibers in tissue engineering, MC3T3-E1 cells were cultured on PCL and PCL/GO-g-PEG scaffolds, thus providing preliminary and comparative proliferation rate assays.